Administrator Sebagai Representasi Deliberatif: Sebuah Bentuk Perbaikan Peran Pelayanan Publik - Mostien (Institut Riset dan Pengembangan Indonesia, 2023)
It is recommended that the role of the public administrator as a representative be deliberative. The aim is to reapply the concept of representation in the context of public administration based on a literature review on the following concepts: 1) representative democracy, (2) representative bureaucracy, and (3) deliberative democracy. It was found that the dominant model of representative democracy was not suitable for guaranteeing the interests of citizens and society and that a representative bureaucracy was unsatisfactory for overcoming the failure of representative democracy. Finding promise in the model of deliberative democracy, consider how recon ceptualization of representation for administrative roles shapes the advancement of civic participation in order to improve the quality of representation. Specifically, the fourth construct is defined to add to the list of the top three: deliberative representations.